Symmetric tungsten triple probe diagnostic for time resolved measurements in plasma discharge - Ali, A. (IOS Press, 2015)
In this research work, time resolved measurements of floating potential, electron temperature and number density were performed in air discharge plasma. A symmetric tungsten triple probe diagnostic and circuitry were developed to diagnose DC discharge at different operating conditions. Motivation behind the direct access of electrical probe diagnostic to the plasma chamber was stemmed from the need to characterize the plasma for time resolved measurements of the discharge parameters with high accuracy. The error analysis showed that overall inaccuracy in the measurements for electron temperature and number density remained in the range of 8.2-11.6 and 7.65-13.9, respectively. Traditionally, the error in electrostatic probe measurements is typically 20 for electron temperature and 50 for electron number density. Although these values are sufficiently large, the given analysis on consecutive measurements under same operating conditions yielded the data with high accuracy. The time resolved spectra of floating potential, investigated at all applied voltages, showed negligible variations in potential wave shape over time. However, the pressure dependent spectra predicted that the floating potential changed into sinusoidal waves of growing amplitude at higher air pressures. Overall floating potential was appreciably decreased with rise in air pressure. Â© 2015 - IOS Press and the authors. All rights reserved.